Valores organizacionais, suporte social e organizacional no trabalho: um estudo no setor bancário - Andrade, Taís de (2010)
This research was developed in order to understand the influence of organizational values on the perception of social and organizational support at work, considering the perspective of both employees and managers from the public and private banking sectors. Therefore, a descriptive research of survey type was carried out, drawing on quantitative and qualitative methodologies for the collection and analysis of results. Initially, in the quantitative stage, 332 employees from the banking industry participated, and they answered a questionnaire developed by the Inventory Model Profiles Organizational Values (IPVO) de Oliveira and Tamayo (2004); Scale Perceived Social Support at Work (EPSST) from Gomide Jr., Guimaraes and Damasio (2004), and Perception Scale Organizational Support Office (EPSO), validated in Brazil by Siqueira (1995). In a second step, nine managers from the banks researched participated in the study, and they answered semi-structured interviews, based on the literature about organizational values and organizational and social support at work. Data obtained in the quantitative stage were analyzed with the help of SPSS software to perform statistical tests, while data obtained in the qualitative phase were analyzed qualitatively through the themes determination and the content analysis. The main results show that the main organizational values of banks, as observed for both employees and managers were the Dominion and the Prestige, while the values Well-being, Autonomy and Self-Realization occupied lower positions in the hierarchy. In relation to the social support at work, the highest incidence was attributed to Informational Social Support, and the lowest priority was assigned to Emotional Social Support. In addition, Organizational Support presented the lowest incidence rate, when compared to the types of social support at work. Besides that, the multiple regression analysis revealed that the model with greater explanatory power was often represented by the Organizational Support, whose variance was explained in 70.2% by the Autonomy and Achievement Domain, and Well-being factors, followed by the model General Support, whose variance was explained in 45,6% for the values Autonomy and Achievement, Prestige and Domain. Thus, we found organizational values influence on the perception of social and organizational support at work.